Towards developing a service delivery improvement model for the Malaysian Hotel sector / Johanudin Lahap, G. Barry O'Mahony and Jim Sillitoe - Lahap, Johanudin; G., Barry O'Mahony; Jim, Sillitoe (Research Management Institute (RMI), 2011)
The Malaysian hotel industry has experienced significant growth in the last 10 years and many hotels in Malaysia are now opulent, new hotels achieving the highest standards of presentation. However, service delivery often lags behind the physical environment, struggles to meet international standards and ergo the expectations ofinternational guests. There are diverse views among service quality researchers as to how to improve service delivery standards. Consequently, this study seeks to develop an appropriate service delivery improvement model that provides a framework that can be used to attract, train, motivate and retain hotel employees. Within the literature many strategies have been presented that are designed to enhance both products and services in a variety of contexts. Among the better known ofthese are Total Quality Management (TQM), Six Sigma (SS), SERVQUAL (SQ), the Relationship Marketing paradigm (RM), Internal Marketing (1M) and Internal Market Orientation (IMO). The general view among scholars, however, is that there is a link between employee satisfaction and job performance. This article examines and analyses the most significant elements of various product and service improvement models, and presents a revised service delivery improvement model as afirst step in customising a modelfor the Malaysian hotel sector. The research concludes that a number of these elements are critical to service improvement, the authors note that the implementation of such a model will need to be further developed with assistance from industry stakeholders in Malaysia.